Penerapan Kerangka Acuan Biomekanik Pada Kasus Fraktur Distal Radius Ulna Dalam Kemandirian Membungkus Makanan - Gidion, Hermito; Sugianto, Jasmine Putri; As’ari, Mahrus; Betty, Purnama (UI Scholars Hub, 2023)
A distal radius fracture is a fracture that occurs when the radius bone, one of the two long bones in the forearm, breaks near the wrist. This paper aims to determine the application of the biomechanical frame of reference in cases of fractures of the distal radius ulna in the independence of wrapping food. This research was conducted by taking the case of a patient, conducting assessment, observation, and intervention on the patient. Specifically, the assessment carried out focuses on range of motion abilities, muscle strength and endurance, pain scale and functional activity abilities. The patient's problems were decreased joint range of motion, muscle strength, and muscle endurance and experienced pain caused by a fracture of the distal radius ulna, so that they experienced difficulties in productivity activities, especially in carrying out food wrapping activities. Occupational therapy provides interventions using a biomechanical approach to help increase the range of motion of the joints, muscle strength and muscle endurance as well as adapting ways for the recovery of patients with distal radius-ulna fractures and increasing the patient's productivity abilities as a food seller.